Public Information Officers as agents of change. - Eraldo, Gerald
This study "Public Information Officers as Agents of Change" evaluates the qualifications and duties of the seven Public Information Officers in the seven municipalities situated in the First Congressional District of Iloilo based on the mandate provided by the Local Government Code of 1991 in line with their role as agents of change. This study also identified the communication tools and strategies employed by the Public Information Officers in their course of duty. Furthermore, this study assesses the awareness of the respondents in the concept of Development Communication as a strategy in bringing change. The results of the study reveal that the Public Information Officers are not functioning as agents of change primarily because most of them do not meet the standard requirements intended in their position. Secondly, the appointment was not made in concurrence to the mandate of the code because of unawareness of the appointing officer (the municipal mayor). The respondents' use of tools and strategies were not maximized as reflected to the frequency of their output in information dissemination. This study also shows the inability of the Public Information Officers in utilizing information as a tool in acting as agents of change.